Pemberdayaan Petani Lele sebagai Pilar Ketahanan Pangan dan Pemenuhan Protein di Wilayah Perdesaan Desa Luwungragi, Kabupaten Brebes Jawa Tengah - Wadli, Wadli; M. Hasdar; Yulianto, Andi; Bashar, Abdul (Jurnal SOLMA, 2026)
Background: The catfish farmer empowerment program in Luwungragi Village, Brebes Regency, was carried out to strengthen local food security through increased productivity, downstreaming of harvested products, and expanding market access. Activities included modern cultivation training, vacuum yellow spiced catfish processing training, digitalization of business management, and the establishment of marketing networks. Method: Implementation was carried out in a participatory manner through five stages: identification, training, mentoring, strengthening networks, and evaluation. Results: showed a decrease in fish mortality from 28% to 11%, an acceleration of the harvest cycle from 95 to 78 days, an increase in harvest yields from 160 kg to 224 kg per cycle, and an increase in profit margins from IDR 2.2 million to IDR 8.5 million per cycle. New processed products and digital marketing increased the competitiveness of partners. Conclusion: . This program has a significant impact on village food security by providing affordable animal protein, increasing income, and strengthening farmer institutions and communities who increasingly understand the benefits of consuming catfish to obtain daily protein.